Aktivitas antihiperglikemia ekstrak kulit dan daun surian (Toona sinensis) pada tikus diabetes (Sprague-dawley) yang diinduksi streptozotocin - Theresia, Rori; Falah, Syamsul; Safithri, Mega (Jurnal Gizi dan Pangan, 2017)
This study aimed to examine the antihyperglycemia activity of ethanol extract of 70% on surian bark and leaves on diabetic rats induced with streptozotocin based on body weight, and fasting blood glucose level. Consist of 28 rats are grouped into 7 groups namely normal, negative control, positive control which given glybenclamide with a dose of 3.22 mg/kg bw, bark extract with dose of 150 mg/kg bw, bark extract with a dose of 300 mg/kg bw, leaf extract with dose 150 mg/kg bw and leaf extract with dose 300 mg/kg bw. Diabetogenic mechanisms was conducted with intraperitoneal injection of streptozotocin at  dose of 50 mg / kg bw. This research was conducted experimentally using complete randomized design (RAL) to analyze the results obtained. Bark extract with a dose of 150 mg/kg bw had a better antihyperglycemia activity compared to the other groups which was showed by the decrease of blood glucose level percentage of 72.83% and this group also had ability to maintain body weight was better than the other groups as well as stable feed consumption during research process.